Complementary Medicine and Nursing in Oncology Development of evidence-based, symptom-related topic guidelines for interprofessional counseling of tumor patients - Kroeger, B.; Kaschdailewitsch, E.; Behzad, Ali; Schmitt, A.; Lohmueller, L.; Valentini, J.; Noack, B.; Froehlich, D.; Horneber, M.; Mahler, C.; Joos, S.; Stolz, R. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-11-18

Enasidenib in IDH-2 mutant AML patients with relapse after allogeneic stem cell transplantation - Vasova, Ingrid; Spörl, Silvia; Guggenberger, Valentin; Berisha, M.; Rech, D.; Behzad, Ali; Brandt, Amelie; Kremer, A.; Mackensen, Andreas; Rösler, Wolf; Winkler, J. (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

Interprofessional Communication about Complementary and Integrative Health (CIH): Development and Implementation of a Training Program - Behzad, Ali; Stein, Barbara; Kaltenbach, Anna; Lohmueller, Lioba; Kroeger, Birgit; Boltenhagen, Ursula; Joos, Stefanie; Klafke, Nadja; Mahler, Cornelia; Stolz, Regina; Valentini, Jan; Horneber, Markus (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-12-16

Interprofessionelle Kommunikation uber,Complementary and Integrative Health" (CIH): Entwicklung und Implementierung eines Training-Programms - Behzad, Ali; Stein, B.; Schmitt, A.; Lohmuller, L.; Kroger, B.; Boltenhagen, U.; Joos, S.; Klafke, N.; Mahler, C.; Stolz, R.; Valentini, J.; Horneber, M. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-11-18

TaKeTiNa Music Therapy for Outpatient Treatment of Depression: Study Protocol for a Randomized Clinical Trial - Behzad, Ali; Feldmann-Schulz, Christoph; Lenz, Bernd; Clarkson, Lucy; Ludwig, Celine; Luttenberger, Katharina; Völkl, Simon; Kornhuber, Johannes; Mühle, Christiane; von Zimmermann, Claudia (Journal of Clinical Medicine, 2024)
Background/Objectives: Depression is a prevalent and debilitating illness that significantly affects psychological and physical well-being. Apart from conventional therapies such as psychotherapy and medication, individuals with depression often lack opportunities for activities that are generally perceived as enjoyable, such as music, meditation, and arts, which have demonstrated therapeutic effectiveness. TaKeTiNa music therapy has been employed as a therapeutic intervention for more than two decades. However, there is a notable absence of well-designed clinical trials investigating its antidepressant effects, a gap we aim to address in our current study. Furthermore, shifts in the progression of depression may manifest both psychologically, by influencing emotional states, and physiologically, by leading to alterations in lipid and sphingolipid metabolism, cortisol levels, and immune system function. Our study seeks to analyze the impact of TaKeTiNa music therapy on both levels. Methods: This is a prospective monocentric randomized waitlist-controlled clinical trial. It investigates the influence of TaKeTiNa music therapy on patients with major depression in an outpatient setting. Therefore, interested persons are randomly assigned to two groups, an intervention group or a control group, after completing a screening procedure. The intervention group starts with an eight-week TaKeTiNa music therapy intervention. The waiting group receives the same therapy program after completing the follow-up period. Blood and saliva sampling as well as responses to questionnaires are obtained at specific time points. Discussion: Our study investigates the effects of TaKeTiNa music therapy, a non-pharmacological antidepressant treatment option, on depressive symptoms. We also address functional and causal immunological changes; hormonal changes, such as changes in cortisol levels; and metabolic changes, such as changes in serum lipids and sphingolipids, during the course of depression. We expect that this study will provide evidence to expand the range of treatment options available for depression.
CRIS-Team Scopus Importer:2024-05-24
Keywords: affective disorder; depression; immune system; music therapy; non-pharmacological therapy; randomized waitlist-controlled trial; translational